Privilege in fraternities and sororities: racial prejudices through the use of formalized recruitment, tradition, and marketing - Gibbs, Caelee Tra (Kansas State University, 2013)
Privilege and its’ impact on the racial and social constructs of fraternity and sorority life is an issue that has plagued the past and continues to determine the future. The examination of literature and the application of both Critical Race Theory and Critical Race Feminist Theory provides the theoretical framework for defining this issue. While White privilege does not answer all questions regarding race and how it determines sorority and fraternity membership, it does seek to address issues surrounding the traditions and customs in fraternity and sorority life. Additionally, in using a Critical Race Feminist perspective it seeks to address issues regarding the formalized sorority recruitment process used by traditionally White sororities and its impact on multicultural students. As a result of the findings within the literature, the traditional practices fraternities and sororities cling to only further draw discriminatory barriers between traditionally White Greek organizations and potential multicultural members. Furthermore, if this issue is not addressed within both higher education and Greek life it could signal further racially dividing issues. With the impact of biracial and multiracial students becoming more prevalent on campuses, student affairs practitioners must work to redefine what race and ethnicity mean in terms of student affiliation and involvement. Future research must study the impact of segregated governing organizations and their impact on creating cohesion between multicultural and traditionally White fraternal organizations.
Keywords: White privilege; Multicultural; Sororities; Fraternities; Hazing; Critical race theory; African American Studies (0296)